O-15 Supportive care in cirrhosis: how an MDT can improve care for patients with advanced liver disease. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Ford-Dunn, Suzanne; Batchelor, Kim; Kriese, Stephen; Thomson, Sam
Abstract : Introduction: Liver disease is the fifth commonest cause of death in the UK: the only major cause of death still increasing (Public Health England, 2015). National data show 73% of deaths occur in hospital (National End of Life Care Intelligence Network, 2012) and few patients are referred to palliative care services (PC) despite complex symptoms and psychosocial needs. Although preferred place of death (PPD) for patients with end stage liver disease (ESLD) is unknown, studies of other diagnoses show the majority of patients prefer to die at home, rather than hospital (Office for National Statistics, 2015). We aimed to increase access to PC for patients with ESLD and ascertain PPD. Methods: We commenced a monthly ESLD MDT, comprising Hepatology and PC Consultants, hospice ESLD Clinical Nurse Specialist (CNS), Alcohol CNS, Social Worker and hospital PC CNS. The MDT reviewed patient needs, coordinated care and initiated referrals to community services. Patients referred to the ESLD CNS received holistic assessment, advance care planning and contingency plans for future acute decompensation events. Results: In the first 12 months of the new MDT there were 43 deaths with ESLD in our locality, 60% in hospital, 37% in community (home/hospice); contrasting to 73% and 26% nationally. 79% of all patients were known to PC at the time of death. Of 22 patients that expressed a PPD, 11 chose home and 11 hospice; none preferred to die in hospital. Of 22 patients under the hospice ESLD CNS, 73% died out of hospital (seven home, nine hospice). 68% of patients under the ESLD CNS died in their preferred place of care. Conclusions: Most patients with ESLD prefer to die out of hospital, consistent with other terminal illnesses. Although ESLD patients present a challenging symptom burden it appears an MDT approach including a dedicated hospice CNS can help increase referrals to PC, and help more patients die in their preferred place.